2017
DOI: 10.15414/jmbfs.2017/18.7.3.242-247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamins on the Quality of Insemination Doses of Bulls

Abstract: To preserve and protect spermatozoa against any possible oxidative damage the addition of natural antioxidants might be the ideal solution which has been investigated worldwide. The composition of the diluents is as follows: 50 µM/L vitamin C with 0.5% DMSO (dimethyl sulfoxide, Sigma, St. Louis, USA); 50 µM/L vitamin E with 0.5% ethanol; each added separately to the spermatozoa with the aim to determine its effect on post-thaw quality of spermatozoa. 20 samples from each control and experimental group were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…As shown in Figure 5a, our results showed that VC protected mitochondrial function by improving Δψm levels in sex-sorted bull sperm, confirming the results in non-sorted sperm in bovine (Hashim, Tvrdá, Greifová, & Lukáč, 2017) and human (Fanaei et al, 2014). It has been proven that VC can prevent intracellular overproduction of ROS (Hashim et al, 2017) and protect mitochondrial function (Fanaei et al, 2014) in sperm, which contributes to explaining the higher Δψm levels in our experiments.…”
Section: Discussionsupporting
confidence: 88%
“…As shown in Figure 5a, our results showed that VC protected mitochondrial function by improving Δψm levels in sex-sorted bull sperm, confirming the results in non-sorted sperm in bovine (Hashim, Tvrdá, Greifová, & Lukáč, 2017) and human (Fanaei et al, 2014). It has been proven that VC can prevent intracellular overproduction of ROS (Hashim et al, 2017) and protect mitochondrial function (Fanaei et al, 2014) in sperm, which contributes to explaining the higher Δψm levels in our experiments.…”
Section: Discussionsupporting
confidence: 88%
“…It also deactivates free radicals, protects the cellular membrane against O 2 free radicals, and prevents the production of ROS [ 54 ]. During cryopreservation, when vitamin E reacts with cryoprotectants, it can efficiently preserve the semen [ 55 , 56 , 57 ]. Vitamins E and C collectively enhance the intra-cytoplasmic semen injection (ICSI) success rate in patients with semen DNA damage and decrease the level of DNA impairment [ 58 ].…”
Section: Antioxidants and Infertilitymentioning
confidence: 99%